Vocal Hygiene Education Program Reduces Surgical Interventions for Benign Vocal Fold Lesions: A Randomized Controlled Trial. (6th August 2018) - Hosoya, Makoto; Kobayashi, Rika; Ishii, Toyota; Senarita, Masamitsu; Kuroda, Hiroyuki; Misawa, Hayato; Tanaka, Fujinobu; Takiguchi, Tetsuya; Tashiro, Masatsugu; Masuda, Sawako; Hashimoto, Sho; Goto, Fumiyuki; et al.
Abstract : Objectives/Hypothesis: Vocal fold polyps and nodules are common benign laryngeal lesions. Currently, the Japanese health insurance system covers surgical interventions. However, the establishment of more cost‐effective conservative methods is required, because healthcare costs are viewed as a major concern, and the government and taxpayers are demanding more economical, effective treatments. In this situation, more suitable vocal hygiene education may be important for the success of cost‐effective conservative treatment. In this study, we developed a novel reinforced vocal hygiene education program and compared the results of this program with those of previous methods of teaching vocal hygiene. Study Design: Multicenter randomized controlled trial. Methods: Patients who visited a National Hospital Organization (NHO) hospital for the surgical indication of hoarseness were included in the study. Before undergoing surgery, 200 patients with benign vocal fold lesions (vocal fold polyps/nodules) were enrolled and randomly allocated to the NHO‐style vocal hygiene educational program (intervention group) or control education program (control group). Two months after enrollment, the patients in both groups underwent laryngeal fiberscopic examinations to determine whether the benign lesions had resolved or whether surgery was indicated for the vocal fold polyps/nodules. Results: After 2 months, in the intervention group, the proportion of lesion resolution (61.3%) was significantly greater than that in the control group (26.3%) ( P  < .001, Fisher exact test). Conclusions: Our results clearly indicate that the quality and features of the education program could affect the outcome of the intervention. We found that a reinforced vocal hygiene education program increased the rate of the resolution of benign vocal fold polyps and nodules in a multicenter randomized clinical trial. Level of Evidence: 1b Laryngoscope, 2593–2599, 2018